The efficacy of Da Chaihu decoction combined with metformin tablets for type 2 diabetes mellitus: A systematic review and meta-analysis - Jia-bin Wang; Yan-xia Wang; Fen Li; Yan-fei Li; Xing-li Li; Pei-yao Huang; Chen Wang; Meng Wang; Jie Qiu; Ke-hu Yang; Wen-wen Qiu; Lu Liu; et al. (Elsevier, 2022)
Objective: To assess the efficacy of Da Chaihu decoction combined with metformin tablets on patients with type 2 diabetes compared with metformin alone. Methods: This systematic review and meta‐analysis is written based on 2020 PRISMA Extension for Chinese Herbal Medicines 2020 (PRISMA-CHM 2020) reporting guidelines. We reviewed all the relevant studies from a search of the following databases from inception to February 2022 without any language restriction: Excerpta Medica Database (EMBASE), Google Scholar, PubMed, Cochrane Library, China National Knowledge Infrastructure (CNKI), VIP Information, Wanfang Data, and the Chinese Biomedical Literature Database(CBM). Data were extracted and the quality was independently evaluated by two reviewers, based on the inclusion and exclusion criteria. Data were analyzed using the Cochrane software RevMan 5.3. Results: Six randomized controlled trials comprising 516 participants were included.The meta‐analysis revealed the Da Chaihu decoction combined with metformin tablets group was significantly superior to the metformin tablets group in terms of fasting blood glucose(FPG) (−0.66 mmol/L; 95 % CI (confidence intervals) [− 1.28, − 0.04]), plasma glucose 2 h after meal (2-h PG) (−1.18 mmol/L; 95 % CI [−1.94, −0.42]) in six RCTs, body mass index (BMI) (−3.07 mmol/L; 95 % CI [−6.89, 0.75]) in three RCTs, glycosylated hemoglobin (HbAlc) (−0.36 mmol/L; 95 % CI [−1.04, 0.31]) in three RCTs, and triglycerides (TG) (−0.76 mmol/L; 95 % CI [−1.37, −0.15]) in two RCTs. In two RCTs, there were significant differences in terms of total cholesterol (TC) (−0.97 mmol/L; 95 % CI [−1.18, −0.76]). Conclusions: Very low-quality research shows that Da Chaihu decoction combined with metformin tablets exert a certain level of efficacy on patients with type 2 diabetes compared with metformin alone. However, random sequence generation methodology was reported in five studies leading to the low quality of the included studies. None of the six studies depicted the blinding method, allocation concealment, selective reporting, and assessed the purity and potency of the product. This observation requires verification through high-quality, multi-center, double-blinded randomized controlled trials, and assesses the purity and potency of the product.